2019
DOI: 10.4312/as.25.1.89-110
|View full text |Cite
|
Sign up to set email alerts
|

Career Service as a Measure to support Employability

Abstract: The paper examines models and activities of career services as a measure to support students’ employability in higher education. It presents a comparative study between the University of Florence (Italy) and the University of Lagos (Nigeria). It starts from a meso-level analysis of service models and data based on institutional university reports. In fact, the literature at international level illustrates the relevance of career service organisations in supporting the educational process. The analysis of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For many college and university students, attending an institution of higher education offers opportunities to create new networks and experiences that allow them to explore different vocational trajectories. Within the higher education sector around the world, CSCs are increasingly viewed as a critical venue for assisting students with their career planning, especially via the dissemination of information related to job-seeking, labor market dynamics and placement opportunities (Terzaroli and Oyekunle, 2019; Usher and Kwong, 2014). At the same time, information and tacit norms gleaned from students’ early life experiences and socialization into different communities of practice (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many college and university students, attending an institution of higher education offers opportunities to create new networks and experiences that allow them to explore different vocational trajectories. Within the higher education sector around the world, CSCs are increasingly viewed as a critical venue for assisting students with their career planning, especially via the dissemination of information related to job-seeking, labor market dynamics and placement opportunities (Terzaroli and Oyekunle, 2019; Usher and Kwong, 2014). At the same time, information and tacit norms gleaned from students’ early life experiences and socialization into different communities of practice (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, while a growing body of research is examining different aspects of CSC operations including students’ satisfaction with CSC services (Usher and Kwong, 2014), and comparative analyses of CSC operations in countries such as China and the USA (Wei et al , 2016), and Italy and Nigeria (Terzaroli and Oyekunle, 2019), there exists little empirical research on the types of information that college students use and/or draw upon to make decisions about careers. In one of the few empirical studies on the topic, Pesch et al (2018) found that undergraduate students in a US university increased engagement in activities that promoted career exploration (e.g.…”
Section: Background: Developmental Theories and Career Information-seeking Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation